THE EFFECT OF DISCUSSION METHOD TOWARDS STUDENTSâ INTEREST IN LEARNING PROCESS SOCIOLOGY AT SMA N 1 RANAH PESISIR KABUPATEN PESISIR SELATAN - jugasa, Yeli putri; Adiyalmon, Adiyalmon; nazmi, Ranti (Pendidikan Sosiologi, 2013)
This research was about lock of students interest in learning sociology itâs cause of students perception that they think sociology be bored and make them feel sleepy. In other hand, method that used by sociology teacher also monotonous in the class. Al most of the students think that sociology is not really good for the people so many they of students choose like science and other at SMAN 1 Ranah Pesisir Kabupaten Pesisir Selatan. The purpose of this research were. 1). How the teacher use this method to improve studetsâ interest at SMAN 1 Ranah Pesisir Kabupaten Pesisir Selatan. 2). The effect of the method that used by the theacer in improving studentsâ interest at SMAN 1 Ranah Pesisir Kabupaten Pesisir Selatan.This research used qualitative and type of the research was descriptive. Informant of the research take with purposive sampling, the informant in this research were teachers and studentsâ. Source of the research were: a). data primer was data which got from interview and observation. b). data secunder was support data which got from school. the technique of data collection used interview, observation, and documentation. The technique of data analysis were collected the data, reduction the data, display or presentation the data and conclusion.The result of the research. Was studentsâ interest used dis cussion method more improving more than used talking method. Teacher method by using discussion method can make student here argumentation and opinion about learning process. Talkative not hod made the students passive in learning process because they only silent in the class. In addition discussion method have long time while the time of study did not suitable by using discussion method, adaptable every method that will used in learning process.